Analisis Pendidikan Karakter Disiplin pada Pembelajaran Daring Siswa Kelas IV MI Miftahus Shibyan Kabupaten Jepara - Fiky Hanaunnadiya; Anita Chandra Dewi Sagala; Suyitno Suyitno (STKIP Andi Matappa Pangkep, 2022)
The purpose of this research was to analyze how the implementation of discipline character education in online learning for fourth grade students of MI Miftahus Shibyan, Jepara Regency. This study uses a qualitative method with a naturalistic approach with descriptive analysis techniques. The results of the analysis of the implementation of disciplined character education by grade IV students showed good results which referred to 3 aspects, namely aspects of teaching and learning compliance, aspects of discipline compliance, and aspects of obedience to study hours. This is based on the results of the questionnaire 19 parents of students obtained the results of 84.7%, the results of observations by researchers 68.4%, and the results of interviews with classroom teachers who stated that student discipline was only improved by increasing enthusiasm for learning. The undisciplined attitude shown by some students was due to laziness and the limitations of the learning media used. The conclusion is that the implementation of character education by students is done quite well in online learning.